Tinjauan Literatur: Faktor-Faktor yang Berhubungan dengan Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri di Indonesia - Dyah Suga Santrika Jaya Wardani (Universitas Airlangga, 2024)
Background: Adolescent girls are among the groups considered to be more susceptible to anemia. Iron deficiency is the most common cause of anemia worldwide. Iron Folic Acid (IFA) tablet serve as a solution to treat anemia in young women. However, there are barriers to compliance with IFA tablet use, with only 1.4% of young women using their iron supplements as recommended. Objectives: This literature review aims to delve deeper into the factors influencing the intake adherence of IFA tablets among Indonesian adolescent girls. Methods: A literature review study was conducted using the PRISMA framework, encompassing stages of identification, sorting, and inclusion. Articles were sourced through databases such as Google Scholar, PubMed, and ScienceDirect, resulting in a total of 15 eligible articles after filtering. Results: Factors associated with IFA tablets intake adherence among Indonesian adolescent girls encompass knowledge, awareness, motivation, interest, self-efficacy, attitude, peer support, family support, household income, father's education, the role of health workers, IFA tablet availability, Hb screening, age, area of residence, teacher involvement, the role of UKS, explanation video media, nutrition diary book, and health applications such as Teenfit and CERIA. Conclusions: Factors associated with consumption compliance among Indonesian adolescent girls include behavioral and psychological factors, social factors, family factors, health and medical factors, demographic factors, school factors, and media and technology factors. Factors contributing to non-compliance in young women when using TTD include forgetfulness, side effects of TTD, sensory stimulation, feeling that they do not need TTD because they are healthy, and limited teacher resources.